Rhizosphere bacteria community and petrol hydrocarbon (PHC) biodegradation in soil planted to field crops (Географический вестник=Geographical bulletin, 2017)
A greenhouse pot experiment was conducted for investigating the capability of agrass (annual ryegrass), a legume (summer vetch), and a crucifer (white mustard) to growin a soil from a former coal gasification site and promote the biodegradation of petrolhydrocarbons (PHCs). Soil concentrations of 1517 mg kg-1 of total petrol hydrocarbons(TPHs), including 71.4 mg kg-1 of total US EPA priority polycyclic aromatichydrocarbons (TPAHs) have caused a significant (P